Relationships of Abdominal Pain, Reports to Visceral and Temperature Pain Sensitivity, Conditioned Pain Modulation, and Heart Rate Variability in Irritable Bowel Syndrome - Jarrett, Monica E. (Neurogastroenterol Motil, 2016)
BACKGROUND/AIMS: Irritable bowel syndrome (IBS) is a heterogeneous condition with a number of pathophysiological mechanisms that appear to contribute to symptom chronicity. One of these is altered pain sensitivity. METHODS: Women between ages 18–45 were recruited through the community. Of those enrolled, 56 had IBS and 36 were healthy control (HC) women. Participants completed questionnaires, kept a four-week symptom diary and had a 12-hour Holter placed to assess night-time heart rate variability including high frequency power (HF), low frequency power (LF), and total power (TP). At mid-follicular phase approximately 80% of women completed a thermal pain sensitivity test with conditioned pain modulation and visceral pain sensitivity using a water load symptom provocation (WLSP) test. RESULTS: As expected, daily abdominal pain was significantly higher in the IBS compared to HC group. There were no differences between the bowel pattern subgroups (IBS-diarrhea [IBS-D], IBS-constipation plus mixed [IBS-CM]). Thermal pain sensitivity did not differ between the IBS and HC groups, but was significantly higher in the IBS-CM group than the IBS-D group. In the WLSP test, the IBS group experienced significantly more symptom distress than HCs and the IBS-CM group was higher than the IBS-D group. Heart rate variability indicators did not differ between the groups or IBS subgroups. Daily abdominal pain was positively correlated with LF and TP in the IBS group. CONCLUSIONS: Despite similar levels of abdominal pain in IBS, the IBS-CM group demonstrated greater sensitivity to both thermal and visceral testing procedures.